HYPERBARIC-OXYGEN THERAPY-INDUCED LIPID-PEROXIDATION IN PREGNANT-WOMEN IN LABOR - (:unkn) unknown (JOURNAL CLINICAL BIOCHEMISTRY & NUTRITION, 1992)
The susceptibility of red blood cells to hydrogen peroxide-induced lipid peroxidation was determined for 30 pregnant women in the second stage of labor before and after hyperbaric oxygen therapy. Thirty non-pregnant women were chosen and studied as healthy controls. The results obtained before and after hyperbaric oxygen therapy were compared, and the oxygen therapy was found to cause a significant increase in erythrocyte susceptibility to lipid peroxidation (p < 0.001), an increased plasma lipid peroxide value (p < 0.001), and a significant decrease in glutathione level (p < 0.001). Osmotic fragility curves showed that oxygen therapy caused the appearance of a population of slightly fragile cells, as evidenced by tailing. Reactive oxygen radical formation, their toxic effects in causing lipid peroxidation, and the possible measures that can be taken in such a case are discussed.
Keywords: LIPID PEROXIDATION; HYPERBARIC OXYGEN; PREGNANCY; TOXICITY; RADICALS; DISEASE; SUSCEPTIBILITY